EFEKTIVITAS PENGGUNAAN WATER TRAP PADA SISTEM UDARA KOMPRESOR TERHADAP TINGKAT KEKILAPAN CAT DALAM PROSES PENGECATAN BODI KENDARAAN - Fatjratul Isnandar; Donny Fernandez; Hasan Maksum; Iffarial Nanda (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: The quality of vehicle body painting results is largely determined by the condition of the compressed air used during the spraying process. Compressor air containing water vapor can cause various surface defects such as blistering, pinholing, orange peel, and fisheye, which directly reduce the gloss level of the paint surface. This study aims to examine the effectiveness of using a water trap in the compressor air system on improving painting quality, measured through gloss values using a gloss meter. A quantitative experimental method was employed with two treatment groups: painting without a water trap and painting with a water trap, each tested three times. Results showed that the average gloss value without a water trap was 98 GU, while with a water trap it was 103.33 GU, representing an increase of 5.44%. An independent t-test revealed a significant difference (t = 7.99; Sig. = 0.001 0.05). It is concluded that the use of a water trap significantly improves painting quality by enhancing the atomization process through reduced moisture content in compressed air.Keywords: Water trap, Gloss meter, Painting, Compressor Air, Atomization.